Exoskeletons for workers: A case series study in an enclosures production line. (May 2022) - Pacifico, Ilaria; Parri, Andrea; Taglione, Silverio; Sabatini, Angelo Maria; Violante, Francesco Saverio; Molteni, Franco; Giovacchini, Francesco; Vitiello, Nicola; Crea, Simona
Abstract: This case-series study aims to investigate the effects of a passive shoulder support exoskeleton on experienced workers during their regular work shifts in an enclosures production site. Experimental activities included three sessions, two of which were conducted in-field (namely, at two workstations of the painting line, where panels were mounted and dismounted from the line; each session involved three participants), and one session was carried out in a realistic simulated environment (namely, the workstations were recreated in a laboratory; this session involved four participants). The effect of the exoskeleton was evaluated through electromyographic activity and perceived effort. After in-field sessions, device usability and user acceptance were also assessed. Data were reported individually for each participant. Results showed that the use of the exoskeleton reduced the total shoulder muscular activity compared to normal working conditions, in all subjects and experimental sessions. Similarly, the use of the exoskeleton resulted in reductions of the perceived effort in the shoulder, arm, and lower back. Overall, participants indicated high usability and acceptance of the device. This case series invites larger validation studies, also in diverse operational contexts.